Belief and Intention towards Design Ethics among Design Undergraduates in Malaysian Higher Education Institutions - B. Balakrishnan; F. Tochinai; H. Kanemitsu; M.F.W. Abdullah; S. Indartono (Высшее образование в России)
This paper reports on the findings of a study by design graduates on their belief and intention on ethical issues in the creative design industry. The study was conducted at two universities (University A and University B) in Malaysia, which included 120 undergraduates in design. A survey was conducted in which a questionnaire was distributed among respondents to determine their degree of agreement with respect to each argument in the questionnaire. The results of the data showed that the belief and intention of design graduates towards design ethics is poor, with the exception of the respondents of University A who have strong belief towards social, environmental and sustainability issues. These results indicate that a well-structured model of design ethics education and effective teaching mechanism for design ethics education should be in place. These would have an impact on students’ belief and intention towards design ethics. As such, the research results serve as a cornerstone from which the current practice of teaching and learning of design ethics education can be more critically examined, so that more changes can be made to the existing curriculum that can help to develop designers with ethical characteristics.